Railroad Building, New York World's Fair 1939 (Grinnell Litho Co.)
Suggesting a gigantic railroad roundhouse, this building is the largest at the Fair. Here are exhibited the latest streamlined trains of America and Europe as well as many of the famous locomotives of railroad history. A miniature mountain is used to dramatize the building of a railroad.